Influencia Del Conocimiento Audiovisual En Las Actitudes De Los Estudiantes De La Escuela De Educación Básica “Miguel De Cervantes” Del Cantón Baba Provincia Los Ríos. - Colina Gonzalvo Lourdes (2015)
Speaking of audiovisual media currently leads necessarily to talk about education, because in modern society the mass media have great influence because they offer children and youth informal education sometimes considered more appealing and interesting than that obtained in the school. This research determines how media influence than ever in educating new generations, tastes and trends shaping public of all ages and even influence how the individual relates to himself, his fellows and the world. The study suggests that educators necessarily to support the school must use the mass media, should know how to use technology, but must also act to restore the oral and written language, invoking imperiously television or audiovisual culture, which is often present in the leisure of students. The proposal made in the investigation, is to train teachers in media as a support to educational work, seeking excellence of the student, with teachers prepared according to modern times.